Trajetória histórica do Colégio Nossa Senhora de Lourdes – Cajazeiras - PB (1928 - 1961) - Araújo, Edinaura Almeida de (2020)
The power relations that were established between the Catholic Church and the governments of Brazil since the first moments of colonization were marked by a strong indoctrination and domination by religious representatives who ventured to explore the new establish a domain from education with religious principles. This strong and almost permanent relationship underwent some changes especially when the Republican regime was introduced in 1889. With separation State/Church, at least from a formal point of view, the newly constituted Republic established itself as a secular State. This new political-institutional structure led the Catholic Church to react and create a series of new action strategies to maintain and recover what had been shaken by the new Republican constitutional perspective. One of the strategies used by the Church was the implementation of a Romanized educational project for Brazil, which greatly elevated the number of confessional colleges. Thus, considering this broad movement, we define as an object of this research the College Of Our Lady of Lourdes, located in Cajazeiras-PB, aimed at offering education to girls under the auspices of the Congregation of the Dorothean Sisters, based on the religious and pedagogical principles guided by the perspective by Paula Frassinetti. In this sense, the main objective of this study is to contribute to the construction of the history of the aforementioned institution from the perspective of the following argument of thesis: The College Of Our Lady of Lourdes, was part of an educational project protected by the Church Catholic Catholic, which consolidated its power as a mediator, organizer and normalizer of educational action, interfering mainly in the process of training new teachers that would ensure the dissemination of Christian moral principles. Thus, in addition to this aspect we highlight that this process, in Paraíba, was more intense in its inner regions, in which we understand assumed particular and specific characteristics. The Dorotheas administered the aforementioned College for eight decades, however we decided to establish the time cut considering the year 1928, when it was created until the year 1961, when the dorotean educational project possibly underwent some changes due to the publication that year of the first LDB. This last time frame actually goes beyond the specificity of the history of the aforementioned College since it is an important reference for the History of Brazilian Education. We developed our discussion contributed in the bibliography research pertinent to the history of education beyond a wide spectrum of documentary sources, especially the "Letters of the House of Cajazeiras" now filed in the Provincial House of the Northeast, located in the City Recife - PE under the reponsability of the Dorothean Sisters. We also consulted some copies of The Press Newspaper and The Flor de Liz Magazine. The entire documentary base was analyzed and interpreted from the references linked to the History of School Institutions, especially taking as a broader orientation the studies conducted by Justino Magalhães (2004) in addition to Paolo Nosella and Esther Buffa (2009), detaining us more specifically in the second part of this study to the concept of school culture from the perspective of Dominique Juliá (2001).